SOCIO-ECONOMIC PREREQUISITES FOR THE INNOVATIVE TRANSFORMATION OF THE EXPORT POTENTIAL OF UKRAINE’S AGRICULTURAL SECTOR - KARPENKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article elucidates the conceptual essence and structural components of the socio-economic prerequisites underpinning the innovative transformation of the export potential of Ukraine’s agricultural sector within the framework of global challenges and ongoing structural reforms. Emphasis is placed on the principal vectors of agricultural production modernization, with particular consideration given to the imperatives of sustainable development, digitalization, ecological transition, and the enhancement of international competitiveness. The study substantiates that Ukraine’s agro-exports remain excessively raw material-oriented, thereby exacerbating the sector’s exposure to price volatility and constraining the generation of higher added value. It is demonstrated that innovative transformation constitutes a decisive factor in augmenting export efficiency through diversification towards high-value processed products, the integration of digital agrotechnologies, the adoption of eco-innovations, and the advancement of logistical infrastructure. An analytical assessment is conducted regarding the current state of social capital, agricultural education, extension services, the investment climate, and regional initiatives, all of which condition the adaptive capacity of agricultural producers to innovation uptake. Particular attention is accorded to farmers’ behavioral patterns, risk perception, and mechanisms of social imitation as indirect determinants of export dynamics via their influence on innovative activity. The article advances a set of institutional and economic approaches to fostering innovative transformation, including the expansion of the support architecture through AKIS, the introduction of preferential financial instruments, the establishment of mentoring platforms, and the development of digital agro-education. The findings underscore that the achievement of synergistic interaction between state institutions, farmers’ associations, and market agents provides a foundation for the consolidation of an export-oriented model of innovative agricultural production. The study concludes that the formulation of a multi-tiered policy framework for the innovative renewal of the agricultural sector is an indispensable prerequisite for sustainable economic growth, the strengthening of competitive positions in the global market, and the enhancement of rural community welfare.
Keywords: innovations; agricultural sector; export potential; farm enterprises; digitalization; socio-economic prerequisites; AKIS; competitiveness; agro-export; agricultural policy